Development of Modern Geographical Thinking in India: Evolution of Geographical Thinking through Ancient Cultures to Modern Times (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Geographical perceptions can be traced from very ancient cultures, although geography as all sciences developed during the Enlightenment, but it was in the early nineteen century when it was firmly established based in many aspects in the Darwinian revolution. Chinese geographical writings are considered the first predecessors, followed and developed during the Greek and Roman times. Pilgrimages, travels for trade and the discovery of new lands contributed significantly to the geographical knowledge, as it did the astronomical discoveries. The Germans, Humboldt and Ritter, are considered the fathers of modern geography, the first on the line of physical geography and the second on the human aspects. After them and up to the present, new directions have developed within geography, mainly due to the overview of quantitative and technical tools and to the recent globalization.